Coal-based hard carbon material as well as preparation method and application thereof

Through the method of salt-assisted ball milling and/or active gas-assisted ball milling, coal-based raw materials are pretreated to form a disordered carbon skeleton and suitable pore structure, which solves the problem of poor sodium storage performance of coal-based hard carbon materials and significantly improves the electrochemical performance of sodium ion batteries.

CN119774586APending Publication Date: 2025-04-08FUZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411990645.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The poor sodium storage performance of coal-based hard carbon materials in sodium ion batteries leads to low first-term effectiveness, capacity and rate performance of sodium ion batteries.

Method used

The coal-based raw materials are pretreated by salt-assisted ball milling and/or active gas-assisted ball milling to form a disordered carbon skeleton and a suitable pore structure, thereby improving the sodium storage performance of hard carbon materials.

Benefits of technology

It significantly improves the sodium storage performance of coal-based hard carbon anode material, and improves the first-effect, reversible capacity and rate performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774586A_ABST
    Figure CN119774586A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to a coal-based hard carbon material as well as a preparation method and application thereof. The preparation method of the coal-based hard carbon comprises the following steps: carrying out ball milling treatment on coal-based raw material powder in the presence of metal salt and / or active gas to obtain a pretreated material; and carrying out carbonization treatment on the pretreated material in an inert gas atmosphere to obtain the coal-based hard carbon material. According to the method disclosed by the invention, the molecular structure of the coal-based raw material and the microstructure of the obtained hard carbon material can be adjusted by a strategy of pretreating the coal-based raw material through salt-assisted ball milling and / or active gas-assisted ball milling, so that the sodium storage performance of the coal-based hard carbon negative electrode material can be remarkably improved; and the first efficiency, the reversible capacity and the rate capability of the sodium ion battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a coal-based hard carbon material and a preparation method and application thereof. Background Art

[0002] Thanks to the advantages of abundant sodium resources, wide distribution and low cost, sodium-ion batteries (SIBs) have become an effective choice for the next generation of large-scale energy storage devices. The development of low-cost, high-performance negative electrode materials is crucial to promoting the practical application of sodium-ion batteries. Hard carbon materials are currently the first choice for commercial sodium-ion batteries due to their wide sources, easy processing and abundant reserves. However, due to the abundant pores and defects on the surface of hard carbon materials, a thick solid electrolyte interface (SEI) film and irreversible sodium loss are formed on the surface of the hard carbon negative electrode, resulting in the need to improve the first efficiency, rate performance and cycle stability of the hard carbon negative electrode.

[0003] The type of raw materials for hard carbon is directly related to the sodium storage performance of hard carbon. At present, the sources of hard carbon mainly include biomass and its derivatives, polymers, coal, etc. Although biomass is widely available and inexpensive, the consistency of biomass raw materials is poor, resulting in large energy consumption and costs in the actual production process; in addition, the properties of biomass are relatively solidified, making it difficult to optimize secondary modification. Although polymers can regulate the composition of hard carbon raw materials at the molecular level to modify the microstructure of hard carbon, the carbon yield of polymers is very low and the processing cost is high, which is not conducive to practical production. Coal is a naturally occurring carbon precursor. When coal is used as a precursor of hard carbon materials, it has the advantages of abundant sources, high carbon content, and considerable product yield; in addition, coal is a macromolecular three-dimensional network structure formed by aromatic carbon units with various bridge bonds, so coal-based raw materials also have the advantage of adjustable structure. In summary, coal-based raw materials have the advantages of both biomass and polymer precursors. However, since coal tends to form graphitized carbon microcrystals during high-temperature carbonization, the interlayer spacing of hard carbon is small and the sodium storage performance is poor.

[0004] In order to solve the problem of poor sodium storage performance of coal-based hard carbon, pre-oxidation treatment at 300-400°C in air is usually used to control the properties of coal raw materials. However, the current technical route of air pre-oxidation has obvious shortcomings, including incomplete pre-oxidation of raw materials in air, poor oxidation uniformity, and difficulty in precise control of the pre-oxidation process, resulting in poor controllability and uniformity of the microstructure of hard carbon, and poor consistency of sodium storage of coal-based hard carbon. Therefore, it is necessary to develop a more efficient and controllable strategy to control the structure of coal-based hard carbon and improve sodium storage performance.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a method for preparing a coal-based hard carbon material, so as to solve the technical problem that the sodium-ion battery has low initial efficiency, low capacity and poor rate performance due to the poor sodium storage performance of the coal-based hard carbon prepared by the traditional air pre-oxidation method. The method of the present invention pretreats the coal-based raw material by salt-assisted ball milling and / or active gas-assisted ball milling, and the prepared hard carbon material has good sodium storage performance, which can improve the initial efficiency, capacity and rate performance of the sodium-ion battery.

[0007] The second object of the present invention is to provide a coal-based hard carbon material, which is prepared by the method for preparing the coal-based hard carbon material as described above.

[0008] The third object of the present invention is to provide a negative electrode plate, comprising the coal-based hard carbon material as described above.

[0009] A fourth object of the present invention is to provide a sodium ion battery comprising the negative electrode sheet as described above.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A method for preparing a coal-based hard carbon material comprises the following steps:

[0012] In the presence of metal salts and / or active gases, the coal-based raw material powder is ball-milled to obtain a pretreated material; the pretreated material is carbonized in an inert gas atmosphere to obtain the coal-based hard carbon material.

[0013] Preferably, the method for preparing the coal-based hard carbon specifically comprises the following steps:

[0014] S1. The coal-based raw material powder is mixed with the metal salt powder and transferred to a ball mill, an active gas is introduced, and ball milling is performed to obtain the pretreated material;

[0015] S2. washing and drying the pretreated material to remove the metal salt;

[0016] S3. Carbonizing the dried material under an inert gas atmosphere to obtain the coal-based hard carbon material.

[0017] Preferably, the active gas includes at least one of NH3, CO2, and O2.

[0018] More preferably, the active gas comprises a mixture of NH 3 , CO 2 and O 2 .

[0019] More preferably, in the reactive gas, the volume ratio of the NH3, the CO2 and the O2 is 1-3:3-5:2-6.

[0020] Preferably, at 0-40° C. and 1 atmosphere, the ratio of the mass of the coal-based raw material to the volume of the active gas is 20-30 g / L.

[0021] Preferably, the coal-based raw material includes at least one of bituminous coal, lignite, anthracite and asphalt.

[0022] Preferably, the metal salt comprises at least one of nitrate, chloride and acetate; and / or the metal ion in the metal salt comprises Na + , K + 、Zn 2+ Mg 2+ , Cu 2+ At least one of .

[0023] Preferably, the mass ratio of the coal-based raw material to the metal salt is 1-8:1.

[0024] Preferably, the rotation speed of the ball mill is 300-600 r / min, and the time of the ball mill is 4-10 h.

[0025] Preferably, the temperature of the carbonization treatment is 1000-1500°C, the holding time is 1-3h, and the heating rate is 3-8°C / min.

[0026] A coal-based hard carbon material is prepared by the method for preparing a coal-based hard carbon material described in any one of the aforementioned embodiments.

[0027] A negative electrode plate comprises the coal-based hard carbon material described in the above embodiment.

[0028] A sodium ion battery comprises the negative electrode sheet described in the above embodiment.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The method of the present invention utilizes the mechanical force of high-speed ball milling to promote the interaction between metal salt particles and the macromolecular aromatic ring skeleton in the coal-based raw material and destroy it, thereby forming a disordered carbon skeleton, inhibiting the melting and rearrangement of coal during the carbonization process, thereby forming a hard carbon material with a high degree of disorder; and / or, by means of the shearing effect of mechanical force and the chemical reaction of active gases with the edges of unsaturated fatty hydrocarbons and aromatic hydrocarbon side chains in coal, oxygen-containing and / or nitrogen-containing groups are introduced into the molecular structure of the coal-based raw material, which can synergistically regulate the local graphitized areas of hard carbon, nanopores and active sites doped with heterogeneous atoms on the surface, jointly promote the sodium storage capacity of the slope and platform areas of the hard carbon, accelerate the diffusion and transport of sodium ions on the interface, and comprehensively improve the sodium storage performance of the hard carbon.

[0031] The method of the present invention adopts an active gas-coupled metal salt-assisted ball milling strategy to accurately and controllably adjust the molecular structure of the coal-based raw material and the microstructure of the obtained hard carbon material, thereby significantly improving the sodium storage performance of the coal-based hard carbon negative electrode material, and further improving the first efficiency, reversible capacity and rate performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 is a SEM image of the coal-based hard carbon prepared in Example 1 of the present invention;

[0034] Figure 2 is the XRD pattern of the coal-based hard carbon prepared in Example 1 of the present invention;

[0035] Figure 3 The electrochemical performance diagrams of sodium ion batteries prepared using the coal-based hard carbon in Example 1 of the present invention, the coal-based hard carbon in Comparative Example 1, and the coal-based hard carbon obtained by direct carbonization of coal-based raw materials, wherein (a) is a rate performance diagram and (b) is a first-week charge and discharge curve diagram. DETAILED DESCRIPTION

[0036] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0037] A first aspect of the present invention provides a method for preparing a coal-based hard carbon material, comprising the following steps:

[0038] In the presence of metal salts and / or active gases, the coal-based raw material powder is ball-milled to obtain a pretreated material; the pretreated material is carbonized in an inert gas atmosphere to obtain the coal-based hard carbon material.

[0039] The method of the present invention uses salt-assisted ball milling and / or active gas-assisted ball milling to pretreat the coal-based raw materials, which can accurately and controllably adjust the molecular structure of the coal-based raw materials and the microstructure of the hard carbon obtained by carbonization, thereby significantly improving the sodium storage performance of the coal-based hard carbon negative electrode. The mechanical force of ball milling can promote the interaction between metal salt grains and the macromolecular aromatic ring skeleton in the coal-based raw materials and destroy it, forming a disordered carbon skeleton, inhibiting the melting and rearrangement of coal during the carbonization process. With the mechanical shearing effect of ball milling, the active gas can react chemically with the edge of the unsaturated aliphatic hydrocarbon side chain in the coal, introduce oxygen-containing and / or nitrogen-containing groups into the structure of the coal-based raw materials, and can synergistically regulate the local graphitization area of ​​hard carbon, nanopores and active sites doped with heterogeneous atoms on the surface, jointly promote the sodium storage capacity of the slope and platform areas of hard carbon, accelerate the diffusion and transport of sodium ions at the interface, and comprehensively improve the sodium storage performance of hard carbon.

[0040] In some specific embodiments of the present invention, the method for preparing coal-based hard carbon specifically comprises the following steps:

[0041] S1. The coal-based raw material powder is mixed with the metal salt powder and transferred to a ball mill, an active gas is introduced, and the ball milling treatment is performed to obtain a pretreated material;

[0042] S2. The pretreated material is dispersed in water and stirred evenly to dissolve the metal salt, and the metal salt is removed by centrifugal washing and drying;

[0043] S3. The dried material is carbonized under an inert gas atmosphere to obtain a coal-based hard carbon material.

[0044] Metal salts, active gases and ball milling work together. The sodium storage performance of coal-based hard carbon can be better improved by metal salts and active gases assisting ball milling. In the method of the present invention, the metal salt interacts with the macromolecular aromatic ring skeleton in the coal-based raw material during the ball milling process and destroys it to form a disordered carbon skeleton. The metal salt needs to be removed before carbonization to avoid excessive defects or pores due to the presence of metal salts during the carbonization process, resulting in a decrease in the first effect. In step S2, when removing the metal salt, in order to ensure cleanliness, as an example, the water used is deionized water.

[0045] In some specific embodiments of the present invention, the active gas includes at least one of NH3, CO2, and O2, wherein NH3 is used to regulate the nitrogen-containing functional groups of the coal-based raw materials, and CO2 and O2 are used to regulate the oxygen-containing functional groups of the coal-based raw materials. These oxygen groups will inhibit the rearrangement of the carbon structure during the high-temperature carbonization process and promote the formation of hard carbon materials with high disorder. In addition, NH3 and CO2 also have a pore-forming effect, which can simultaneously regulate the pore structure of the coal-based hard carbon. The appropriate amount of active gas components with pore-forming effects can form a suitable pore structure, which is conducive to the diffusion and embedding of sodium ions and can improve the battery capacity. As an example, the active gas can also contain an inert gas, for example, it can be a mixture of NH3 and Ar, a mixture of CO2 and Ar, a mixture of O2 and N2, a mixture of NH3, CO2 and Ar, and the like. When only NH3 and / or CO2 are used as active components, it is better to use it in combination with an inert gas, because both NH3 and CO2 have a pore-forming effect, and excessive use will produce a large number of pores, aggravate the decomposition of the electrolyte, and reduce the first effect.

[0046] In some preferred embodiments of the present invention, the active gas includes a mixture of NH3, CO2 and O2. The three-gas mixture-assisted ball milling has a synergistic regulatory effect on the coal-based raw material. The lack of any one of the gases will lead to a decrease in the electrochemical performance of the hard carbon negative electrode. The simultaneous introduction of NH3, CO2 and O2 can simultaneously introduce oxygen-containing and nitrogen-containing groups into the molecular structure of the coal-based raw material, which can synergistically regulate the local graphitized areas, nanopores and surface heterogeneous atom-doped active sites of the hard carbon, and jointly promote the sodium storage capacity of the slope and platform areas of the hard carbon. In addition, NH3 and CO2 can also prompt the coal-based hard carbon to form a suitable pore structure, which is beneficial to the diffusion and embedding of sodium ions and improves the capacity.

[0047] In some preferred embodiments of the present invention, the volume ratio of NH3, CO2 and O2 in the active gas is 1-3:3-5:2-6, for example, it can be any point value or a range value composed of any two point values ​​in 1:3:6, 1:4:5, 1:5:4, 2:3:5, 2:4:4, 2:5:3, 3:3:4, 3:4:3, 3:5:2; lack of oxygen or too little oxygen will result in poor inhibition of carbon atom rearrangement during the carbonization process, making it difficult to form more local graphitized areas, and too little oxygen will also It will lead to excessive ammonia and carbon dioxide content, causing a large number of pores, aggravating electrolyte decomposition and reducing the initial efficiency; too much oxygen will lead to too low ammonia and carbon dioxide content, reducing the regulation effect of nitrogen-containing functional groups and the synergistic regulation of oxygen-containing functional groups by carbon dioxide and oxygen. At the same time, too little ammonia and carbon dioxide will cause the hard carbon to lack a suitable pore structure, which is not conducive to the diffusion and embedding of sodium ions, resulting in reduced capacity; therefore, the ratio of NH3, CO2 and O2 needs to be controlled within an appropriate range to achieve better results.

[0048] In some specific embodiments of the present invention, the amount of active gas is limited by the ratio of the mass of the coal-based raw material to the volume of the active gas. At 0-40°C and one atmosphere of pressure, the ratio of the mass of the coal-based raw material to the volume of the active gas is 20-30 g / L. For example, it can be any point value among 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L, 30 g / L, or a range value consisting of any two point values.

[0049] In some specific embodiments of the present invention, the coal-based raw material used includes at least one of bituminous coal, lignite, anthracite, and asphalt.

[0050] In some specific embodiments of the present invention, the metal salt used includes at least one of nitrate, chloride, and acetate; and / or the metal ion in the metal salt used includes Na + , K + 、Zn 2+ Mg 2+ , Cu 2+ At least one of; for example, the metal salt used may be NaCl, NaNO3, CH3COONa, MgCl2, ZnCl2, CuCl2, KCl, and the like.

[0051] In some specific embodiments of the present invention, the mass ratio of the coal-based raw material to the metal salt is 1-8:1, for example, it can be any point value among 1:1, 2:1, 4:1, 6:1, 8:1 or a range value consisting of any two point values.

[0052] In some specific embodiments of the present invention, the ball milling speed is 300-600r / min, for example, it can be any point value among 300r / min, 400r / min, 500r / min, 600r / min, or a range value consisting of any two points; the ball milling time is 4-10h, for example, it can be any point value among 4h, 6h, 8h, 10h, or a range value consisting of any two points.

[0053] In some specific embodiments of the present invention, the temperature of the carbonization treatment is 1000-1500°C, for example, it can be any point value among 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, and 1500°C, or a range value consisting of any two point values; the holding time is 1-3h, for example, it can be any point value among 1h, 1.5h, 2h, 2.5h, and 3h, or a range value consisting of any two point values; the heating rate is 3-8°C / min, for example, it can be any point value among 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, and 8°C / min, or a range value consisting of any two point values.

[0054] A second aspect of the present invention provides a coal-based hard carbon material, which is prepared by the method for preparing a coal-based hard carbon material described in any one of the aforementioned embodiments.

[0055] A third aspect of the present invention provides a negative electrode plate, comprising the coal-based hard carbon material described in the aforementioned embodiment.

[0056] In some specific embodiments of the present invention, the method for preparing the negative electrode sheet comprises the following steps:

[0057] The hard carbon material described in the above embodiment is mixed with a conductive agent, a binder and water to form a slurry, and the slurry is coated on a copper foil by scraping and then dried to obtain the product.

[0058] In some specific embodiments of the present invention, the binder is obtained by dissolving a composite powder of dextran sulfate and polyethylene oxide in deionized water, the mass percentage of the composite powder is 1%-3%, wherein the mass ratio of dextran sulfate to polyethylene oxide is 8-10:1.

[0059] A fourth aspect of the present invention provides a sodium ion battery, comprising the negative electrode sheet described in the aforementioned embodiment.

[0060] In some specific embodiments of the present invention, the electrolyte of the sodium ion battery includes NaPF6 and a solvent, the solvent used includes at least one of DME, DEGDME, and TEGDME, and the concentration of NaPF6 is 0.5-2M.

[0061] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.

[0062] Example 1

[0063] S1. Weigh 4g lignite and 1g NaCl into a mortar and stir them thoroughly. Put the mixed powder and ball milling beads into a ball mill (the mass ratio of the raw material to the ball milling beads is 1:20). At room temperature, evacuate the ball mill to -0.1Mpa to exhaust the air in the ball mill, and then introduce active gas until the pressure in the ball mill is one atmosphere. The volume of the ball mill is 150ml. The active gas is a mixed gas of NH3, CO2 and O2. The volume ratio of the three gases is controlled by the flow ratio of the addition process. The flow rate of the gas addition process is precisely controlled by an external flow meter of the ball mill. In this embodiment, the volume ratio of NH3, CO2 and O2 is controlled at 3:3:4. After the ventilation is completed, the ventilation valve is closed, the ball mill is started, and the ball mill is milled at a speed of 500r / min for 8h to obtain a pretreated material;

[0064] S2. The pretreated material was dissolved in water, magnetically stirred for 6 h, washed three times by centrifugation with water and ethanol, and dried in an oven at 80 ° C for 12 h;

[0065] S3. Weigh 1 g of the material dried in step S2, spread it flat in a crucible, heat it to 1300°C at a heating rate of 5°C / min in a tube furnace under an inert gas atmosphere, and carbonize it at 1300°C for 2 hours to obtain a hard carbon negative electrode material.

[0066] Example 2

[0067] Example 2 is similar to Example 1, with the only difference being that O2 in the active gas is replaced with an equal amount of CO2, that is, the active gas is a mixture of NH3 and CO2, and the volume ratio of NH3 to CO2 is 3:7. The other conditions are the same as those in Example 1.

[0068] Example 3

[0069] Example 3 is similar to Example 1, with the only difference being that CO2 in the active gas is replaced with an equal amount of O2, that is, the active gas is a mixture of NH3 and O2, and the volume ratio of NH3 to O2 is 3:7. The other conditions are the same as those in Example 1.

[0070] Example 4

[0071] Example 4 is similar to Example 3, with the only difference being that NH3 in the active gas is replaced with an equal amount of CO2, that is, the active gas is a mixture of CO2 and O2, and the volume ratio of CO2 to O2 is 3:7. The other conditions are the same as those in Example 3.

[0072] Example 5

[0073] Example 5 is similar to Example 1, with the only difference being that only NH 3 is used as the active gas, and the other conditions are the same as those of Example 1.

[0074] Example 6

[0075] Example 6 is similar to Example 5, with the only difference being that a mixture of NH 3 and Ar is used as the active gas, the volume ratio of NH 3 to Ar is 6:4, and the other conditions are the same as in Example 5.

[0076] Example 7

[0077] Example 7 is similar to Example 1, with the only difference being that metal salt-coupled active gas-assisted ball milling is performed in stages, i.e., after a mixture of metal salt and coal-based raw material is placed in a ball mill, the air in the mill is first evacuated and then a mixture of Ar, CO2, and O2 in a volume ratio of 3:3:4 is introduced and ball milled for 4 hours. The gas in the mill is then exhausted and a mixture of NH3 and Ar in a volume ratio of 3:7 is introduced and ball milled for 4 hours. The other conditions are the same as in Example 1.

[0078] Example 8

[0079] Example 8 is similar to Example 1, with the only difference being that salt-assisted ball milling is performed under an inert atmosphere without active gas assistance, that is, the active gas in Example 1 is replaced with an equal amount of Ar, and the other conditions are the same as in Example 1.

[0080] Example 9

[0081] Example 9 is similar to Example 1, except that no metal salt is added, and only active gas is introduced for auxiliary ball milling. The other conditions are the same as those of Example 1.

[0082] Comparative Example 1

[0083] Comparative Example 1: The coal-based raw material was pretreated by the conventional method of pre-oxidation by heating in air. The pre-oxidation temperature was 350°C and the time was 1 hour. The carbonization process was the same as that in Example 1.

[0084] Test example

[0085] The specific surface area of ​​the coal-based hard carbon materials obtained in each embodiment and comparative example was tested, and the coal-based hard carbon materials obtained in each embodiment and comparative example were assembled into a sodium ion battery and the electrochemical performance of the battery was tested. The assembly process of the battery is as follows:

[0086] Coal-based hard carbon material, conductive agent and binder were weighed in a mass ratio of 85:10:5, deionized water was added to prepare a slurry, and the slurry was scraped on a copper foil and dried in a vacuum oven at 80°C for 12 hours to obtain a hard carbon negative electrode, wherein the binder was an aqueous solution of a composite powder of dextran sulfate and polyethylene oxide (mass ratio 9:1), and the mass percentage of the composite powder was 2%; the hard carbon negative electrode was cut into discs, and button cells were assembled with sodium as the counter electrode and 1M NaPF6 / DME as the electrolyte. The charge and discharge performance of the button battery was tested at room temperature using the LandCT2001A battery test system, with a voltage range of 0.01-2.5V and a current density of 0.1C-5C.

[0087] The test results are shown in Table 1.

[0088] Table 1

[0089]

[0090] It can be seen from the data in Table 1 that the electrochemical performance of the sodium ion batteries prepared from the hard carbon materials in the embodiments of the present invention are better than those in the comparative examples, indicating that the method of the present invention can significantly improve the problems existing in the traditional pre-oxidation method.

[0091] The mixed ball milling assisted by NH3, CO2 and O2 has a synergistic regulatory effect on the structure of coal-based raw materials. The lack of O2 makes it difficult to effectively regulate the coal-based structure, the rearrangement of carbon atoms in the carbonization process cannot be suppressed, and it is difficult to form a larger number of local graphitized areas; while excessive NH3 and CO2 will cause a large number of pores, aggravate the decomposition of the electrolyte, and reduce the initial efficiency; if there is a lack of CO2 or NH3, although it is beneficial to improve the initial efficiency of hard carbon, the lack of suitable pore structure is not conducive to the diffusion and embedding of sodium ions, so the capacity is relatively low; when NH3 is used alone as the active gas, a large number of pores are generated due to excessive NH3, the specific surface area is too high, and the initial efficiency is reduced; by comparing Example 1 and Example 7, it can be seen that when the volume ratio remains unchanged, CO2, O2 and NH3 are introduced in stages, and the electrochemical performance of the hard carbon material decreases, indicating that pre-mixing NH3, CO2 and O2 can more effectively realize the structural regulation of coal-based raw materials and improve the sodium storage performance, indicating that there is a synergistic effect between the three gases.

[0092] From the comparison between Example 1 and Example 8, it can be seen that the electrochemical performance of the hard carbon material is reduced when only salt-assisted ball milling is performed, which fully demonstrates the effect of active gas in optimizing the structure of coal-based raw materials; and from the comparison between Example 1 and Example 9, it can be seen that the electrochemical performance of the hard carbon material is also reduced when only active gas-assisted ball milling is performed, which shows that the addition of salt can also promote the interaction between metal salt grains and the macromolecular aromatic ring skeleton in the coal-based raw material through mechanical force and destroy it, and also promote the formation of local graphitization of hard carbon. Therefore, the hard carbon capacity of the ball milling without salt assistance is also low; therefore, the use of active gas and metal salt to jointly assist ball milling to treat coal-based raw materials has a better structural regulation effect and the obtained coal-based hard carbon has better performance, which can fully demonstrate that there is a synergistic effect between active gas and metal salt assisted ball milling, which jointly promotes the sodium storage performance of hard carbon.

[0093] Figure 1 This is the SEM image of the hard carbon material prepared in Example 1. It can be seen from the figure that the coal-based hard carbon presents an irregular block-shaped particle structure. There are pores and cracks on the surface of the particles, which are conducive to the infiltration of the electrolyte, but there is no obvious pore structure, indicating that the specific surface area of ​​the material is low (see Table 1), which is beneficial to improving the primary effect of the hard carbon (reaching 93.2%).

[0094] Figure 2 This is the XRD diagram of the hard carbon material prepared in Example 1, which shows that the obtained hard carbon material presents a disordered amorphous structure, which is different from the hard carbon structure with a high degree of graphitization obtained by direct carbonization of common coal-based raw materials. This disordered structure has a larger interlayer spacing, which is conducive to sodium ion storage.

[0095] Figure 3The electrochemical performance comparison diagram of the sodium ion battery assembled from the hard carbon material prepared in Example 1, the hard carbon material prepared by the traditional pre-oxidation method in Comparative Example 1, and the hard carbon material obtained by direct carbonization of the same coal-based raw materials, wherein (a) is the rate performance diagram, and (b) is the first week charge and discharge curve diagram. It can be seen from the figure that the rate performance of the hard carbon material treated by the method of the present invention is significantly improved, and the first efficiency is also greatly improved, reaching 93.2%.

[0096] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing a coal-based hard carbon material, characterized in that: The following steps are involved: In the presence of metal salt and / or active gas, the coal-based raw material powder is subjected to ball milling treatment to obtain a pretreated material; The pretreated material is carbonized under an inert gas atmosphere to obtain the coal-based hard carbon material.

2. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The specific steps include: S1. The coal-based raw material powder is mixed with the metal salt powder and transferred to a ball mill, an active gas is introduced, and ball milling is performed to obtain the pretreated material; S2. washing and drying the pretreated material to remove the metal salt; S3. Carbonizing the dried material under an inert gas atmosphere to obtain the coal-based hard carbon material.

3. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The active gas includes at least one of NH3, CO2, and O2.

4. The method for preparing a coal-based hard carbon material according to claim 3, characterized in that: The active gas includes a mixed gas of NH3, CO2 and O2.

5. The method for preparing a coal-based hard carbon material according to claim 4, characterized in that: In the active gas, the volume ratio of the NH3, the CO2 and the O2 is 1-3:3-5:2-6.

6. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: At 0-40° C. and one atmosphere of pressure, the ratio of the mass of the coal-based raw material to the volume of the active gas is 20-30 g / L.

7. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The coal-based raw material includes at least one of bituminous coal, lignite, anthracite, and asphalt; (2) the metal salt comprises at least one of nitrate, chloride and acetate; and / or the metal ion in the metal salt comprises Na + , K + 、Zn 2+ Mg 2+ , Cu 2+ At least one of; (3) The mass ratio of the coal-based raw material to the metal salt is 1-8:1; (4) The rotation speed of the ball mill is 300-600 r / min, and the time of the ball mill is 4-10 h; (5) The temperature of the carbonization treatment is 1000-1500°C, the insulation time is 1-3h, and the heating rate is 3-8°C / min.

8. A coal-based hard carbon material, characterized in that: The coal-based hard carbon material is prepared by the preparation method of any one of claims 1 to 7.

9. A negative electrode plate, characterized in that: Includes the coal-based hard carbon material as described in claim 8.

10. A sodium ion battery, characterized in that: Including the negative electrode sheet as described in claim 9.